Exploring the Governance of Artificial Intelligence Ethics: Current Issues and Challenges - Zhang, Jiumei; Li, Weiqiang; Wang, Liping (International Journal of Global Economics and Management, 2024)
This paper delves into the current state, challenges, and issues in the governance of artificial intelligence (AI) ethics, proposing an ethical risk assessment model and governance strategies. The article begins by summarizing the ethical issues arising from the rapid development of AI technology and their impact on society, including privacy invasion, algorithmic bias, and unclear accountability. It then analyzes the limitations of current AI ethics governance, including deficiencies in governance systems and tools, ambiguity in ethical principles, and a lack of public awareness and international cooperation. Building on this, the paper introduces a comprehensive ethical risk assessment model that emphasizes the consideration of multidimensional factors and the importance of dynamic updates. Furthermore, it constructs a comprehensive governance framework that includes mechanisms for prevention, response, and remediation to effectively manage ethical risks. Finally, the article suggests enhancing the clarity and implementation of ethical principles, increasing public awareness, and fostering international cooperation, while looking forward to future research directions, including the application of interdisciplinary research methods to promote harmonious development between technology and ethics.